Damage assessment of bridges using compound SHM- signal processing and communication challenges - Soman, Rohan N.; Onoufriou, Toula; Kyriakides, Marios (My University, 2013)
A novel compound Structural Health Monitoring (SHM) method as well as some signal processing and communication challenges for a robust methodology are presented in this paper. The performance of the two-step SHM method is compared to some other established damage detection techniques. The proposed method was found to identify the location of local damage more accurately than the other methods. Significant signal processing and communication aspects still need to be addressed in order to enhance the robustness of the method. © 2013 EURASIP.
Keywords: Long Span Bridges; Signal Processing and Communication Challenges; Structural Health Monitoring; Wireless Sensor Network